China’s “One belt, one way” strategic project and the causes of sinophobic sentiment in Kazakhstan - Н.А., Алдабек; А.А., Тургенбай; М.Б., Асыл (Journal of Oriental Studies, 2020)
In this unstable world, where the future of not only nation-states, but of humanity as a whole is in an obscure situation, and the decisive destinies of nations, political elites and intellectual circles are not able to find solutions to many pressing problems, confident steps by the Chinese government to the future, on one hand, inspire great hope and, on the other hand, inspire a threat. In this regard, many studies are actively conducted in the scientific community regarding the modernization of China and from the pro-Chinese, as well as from the anti-Chinese point of view on this problem. The Chinese experience is interesting to everyone, but it is well known that the world community is not yet ready to adopt a Chinacentrist approach to development instead of the traditional Eurocentric approach. Despite the fact that Kazakhstan’s leaders speak of close relations with the Chinese government, “strategic partnership” and “mutual cooperation”, we must admit that on an informal level, tension between the two countries is growing today. In connection with this trend, the article discusses the relationship between Kazakhstan and China. The values and benefits for Kazakhstan of the Chinese strategy “One Belt, One Way” are noted. It also analyzes the issue of sinophobia in Kazakhstan, the causes and consequences for both countries. Key words: China, sinophobia, “One belt One road”, Central Asia, conflicts, politic.